The Effectiveness of Administrative Dispute Resolution Through the Administrative Court and the Ombudsman in Administrative Disputes - Dea Puspitasari; Restu Ramania; Santana Suryapringgana; Teguh Abdurrohman Shodiq; Taufiq Alamsyah (Journal of Human Interaction and Social Studies, 2026)
This study examines the effectiveness of administrative dispute resolution through the State Administrative Court (PTUN) and the Ombudsman of the Republic of Indonesia within Indonesia’s administrative law system. It employs a normative-doctrinal legal research design supported by comparative analysis of statutory instruments, doctrinal literature, and institutional frameworks governing administrative justice. The findings indicate a structural dichotomy between PTUN as a judicial body producing binding decisions and the Ombudsman as a supervisory institution issuing non-binding recommendations. This divergence generates an enforcement gap, particularly in the execution of PTUN judgments and the voluntary nature of Ombudsman compliance. The study further reveals fragmented coordination between both institutions, despite overlapping jurisdictional objects in administrative disputes. Such fragmentation reduces the overall effectiveness of administrative justice in ensuring legal certainty, accessibility, and substantive fairness. The research concludes that neither mechanism independently achieves optimal effectiveness without institutional integration. Strengthening normative harmonization, improving enforcement mechanisms, and clarifying procedural linkages are necessary to enhance system performance and public legal protection. The study contributes to administrative law discourse by proposing a conceptual framework for integrated administrative justice combining adjudicative and supervisory functions.